Preparation method and application of high-performance polyarylether battery diaphragm

By synthesizing and liquid-phase crosslinking polyarylether copolymers, a porous membrane with a triazine ring structure is formed, which solves the shortcomings of the existing lithium-ion battery separators in terms of thermal stability, flame retardancy and impact resistance, and realizes the preparation of high-performance lithium-ion battery separators, which significantly improves the battery's performance.

CN119905773AActive Publication Date: 2025-04-29CHENGDU UNIV

Patent Information

Application Number
CN202510158489.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-04-29
Estimated Expiration
2045-02-13

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators are insufficient in terms of thermal stability, flame retardancy and impact resistance, which affects the cycling performance and safety of the battery.

Method used

A high-performance polyarylether battery separator is used to prepare a high-performance polyarylether copolymer, a low-benzonitrile group content is synthesized, a polyarylether copolymer containing a triazine ring structure is formed by liquid phase crosslinking, and a porous film is formed by electrospinning film formation and solution phase transfer film formation.

Benefits of technology

The prepared polyarylether battery separators have the characteristics of high flame retardant, high strength, high temperature and impact resistance, which significantly improve the performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905773A_ABST
    Figure CN119905773A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a high-performance polyarylether battery diaphragm. The preparation method comprises the following steps: synthesizing a polyarylether (sulfone or ketone) copolymer with low cyanophenyl group content; dissolving the polyarylether (sulfone or ketone) copolymer in a high-boiling-point solvent, performing liquid-phase thermal crosslinking reaction to obtain a crosslinked crude product, purifying the crosslinked crude product to obtain polyarylether containing a triazine ring structure, and retaining part of the high-boiling-point solvent as a solid pore-forming agent in the purification process; and treating the polyarylether containing the triazine ring structure by adopting an electrostatic spinning membrane forming method or a solution phase transfer membrane forming method to form a porous membrane structure, and drying the porous membrane to obtain the high-performance polyarylether battery diaphragm. The polyarylether battery diaphragm has the characteristics of high flame retardance, high strength, high temperature resistance, impact resistance and the like, can be practically applied to lithium ion batteries, sodium ion batteries and the like, and improves the use performance of the batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery materials, and in particular to a preparation method of a high-performance polyarylether battery separator and application thereof. Background Art

[0002] High-performance polymers have attracted extensive attention in the fields of aviation, aerospace, weapons and equipment, and electronic devices due to their light weight, high strength, high temperature resistance, and impact resistance. Compared with thermosetting resins, thermoplastic resins have high flexibility and can be repeatedly processed and reused, but their heat resistance and overall rigidity are lower than those of thermosetting resins. Therefore, the combination of the two has been more widely studied in recent years.

[0003] With the continuous development of industrial technology, the world's demand for energy is increasing. With the gradual scarcity of traditional fossil energy such as oil and coal and the increasingly severe environmental protection problems, lithium-ion batteries have been widely used in new energy vehicles, aerospace vehicles and other fields. Because of its advantages such as high energy density, long cycle life and low self-discharge rate, it is a potential energy source that integrates renewable resources and high-power applications. Lithium-ion batteries are mainly composed of positive electrodes, negative electrodes, diaphragms, electrolytes and shells. Among them, the diaphragm is one of the important components in lithium-ion batteries that does not directly participate in electrochemical reactions, but its properties, structure and composition have a great influence on the safety and electrochemical performance of the battery. Its basic function is to prevent the positive and negative electrodes from directly contacting each other to cause short circuits, store liquid electrolytes and provide channels for lithium ions to migrate during charging and discharging. The diaphragms currently used in the market are mainly polyolefin microporous membranes, such as polyethylene (PE), polypropylene (PP), etc., but their thermal stability, flame retardancy and impact resistance are still insufficient, which has a great impact on the cycle performance and safety of lithium batteries. In the related art, for example, Chinese invention patent CN 112898560 B discloses a poly(arylether nitrile) porous membrane for battery separator obtained by phase transfer method, but its heat deformation temperature, mechanical strength and flame retardant properties are still insufficient to meet the application requirements. The crosslinking temperature of poly(arylether nitrile) solid phase crosslinking is high, the molecular chain movement is insufficient, the product structure is uneven, and the degree of crosslinking is not easy to control. It is easy to form a network-like thermosetting structure and cannot be dissolved again. If a porous membrane is prepared in advance and then solid phase thermal crosslinking is performed, the pore structure of the membrane will collapse again.

[0004] Therefore, there is an urgent need to develop a battery separator that is resistant to high temperatures, has high strength, is impact-resistant and flame-retardant, has a stable preparation process and is easy to operate. Summary of the invention

[0005] In order to solve the above problems, the present invention proposes a preparation method and application of a high-performance polyarylether battery separator. The polyarylether battery separator has the characteristics of high flame retardancy, high strength, high temperature resistance and impact resistance, and can be used in lithium ion, sodium ion and other batteries to improve the performance of the battery.

[0006] In order to achieve the above object, the present invention proposes a method for preparing a high-performance polyarylether battery separator, which comprises the following steps: (1) Synthesis of polyarylene ether copolymers with low benzonitrile group content; (2) dissolving the polyarylether copolymer in a high boiling point solvent, heating under the action of the high boiling point solvent to carry out liquid phase crosslinking to obtain a crosslinked crude product, and purifying the crosslinked crude product to obtain a polyarylether copolymer containing a triazine ring structure, wherein a portion of the high boiling point solvent is retained during the purification process as a solid pore-forming agent; (3) The polyarylether copolymer containing a triazine ring structure is treated by electrospinning and solution phase transfer to form a porous membrane, and a high-performance polyarylether battery separator is obtained after drying.

[0007] According to a method for preparing a high-performance polyarylether battery separator of the present invention, the method first synthesizes a polyarylether copolymer with a low benzonitrile group content, wherein the benzonitrile structure enables the polyarylether main chain to have the ability to cross-link to form a triazine ring structure, and the low content of cyano groups does not result in too dense cross-linking points; liquid-phase cross-linking is performed in a high-boiling point solvent to form a multi-branched macromolecule with triazine rings as cross-linking points between polyarylether molecular chains, while gelation due to excessive cross-linking is not generated; in addition, a portion of the high-boiling point solvent is retained in the product during the purification process as a solid pore-forming agent for the subsequent porous membrane preparation, thereby improving the uniformity of the pores in the separator. The polyarylether battery separator prepared in this way has the characteristics of high temperature resistance, high strength, impact resistance and excellent flame retardancy, and can be used in lithium ion, sodium ion and other batteries, thereby improving the performance of the battery. Compared with the separator prepared by the phase inversion method using polymer raw materials in general, the present invention forms a triazine ring structure after the polymer is pre-crosslinked through the solution, and the polymer is converted from a linear molecule to a branched structure with a higher molecular weight, thereby further improving the corresponding performance of the material, so that the polyarylether battery separator has the characteristics of high flame retardancy, high strength, high temperature resistance and impact resistance.

[0008] Optionally, the content of benzonitrile in the polyarylene ether copolymer with low benzonitrile group content is less than or equal to 35%.

[0009] Furthermore, the polyarylether copolymer is polyarylether nitrile sulfone or polyarylether nitrile ketone, and the proportion of the aromatic sulfone or aromatic ketone structure is greater than or equal to 65% and less than 100%.

[0010] Optionally, step (1) includes: Dihydric phenol, 2,6-dichlorobenzonitrile or 2,6-difluorobenzonitrile and 4,4-dichlorodiphenyl sulfone or 4,4-dichlorobenzophenone are dissolved in an organic solvent N-methylpyrrolidone (or N,N-dimethylformamide or N,N-dimethylacetamide or cyclopentane sulfone) and toluene, and a nucleophilic substitution condensation polymerization reaction is carried out with potassium carbonate as a catalyst; after the viscosity no longer increases, toluene is evaporated, and the product is poured into deionized water, and purified to obtain the polyarylene ether copolymer with a low benzonitrile group content.

[0011] Optionally, the molar ratio of the 2,6-dichlorobenzonitrile or 2,6-difluorobenzonitrile, the dihydric phenol and the 4,4-dichlorodiphenyl sulfone or 4,4-dichlorobenzophenone is n:(n+m):m, wherein n / (n+m)<35%.

[0012] Optionally, the high boiling point solvent is one or more solvents such as diphenyl sulfone, cyclopentane sulfone, glycerol, etc., whose boiling points are above the cross-linking temperature of the system.

[0013] Optionally, in step (2), the temperature of the liquid phase heat treatment cross-linking is 290°C to 340°C, and the cross-linking time is 1 h to 4 h. At the same time, the cross-linked product can be accurately controlled by the viscosity of the solution so that it does not gel and lose the ability to dissolve and form a film again; specifically, it can be accurately detected by manual stirring and observation or by inserting an online electronic viscosity meter.

[0014] Optionally, in step (2), purification is performed by crushing the cross-linked crude product and washing it with an organic solvent. The purification process can retain 0-20% of the high boiling point solvent in the product as a solid pore-forming agent for the subsequent preparation of the porous membrane, thereby improving the uniformity of the pores in the diaphragm and optimizing the pore structure.

[0015] Optionally, the organic solvent is one or more of ethanol, acetone, and butanone.

[0016] In a second aspect, the present invention provides the use of the high-performance polyarylether battery separator prepared by the above preparation method in lithium-ion batteries or sodium-ion batteries.

[0017] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the structure and synthesis cross-linking of poly(arylether nitrile sulfone) according to an embodiment of the present invention; Figure 2 is an infrared radiation thermal imaging image of a polyarylethernitrilesulfone diaphragm prepared by different cross-linking reaction times according to an embodiment of the present invention; Figure 3It is a comparison chart of the long cycle performance of lithium-ion batteries assembled with the diaphragm according to the embodiment of the present invention at room temperature and high temperature. DETAILED DESCRIPTION

[0019] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.

[0020] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0021] The test materials used in the present invention are all common commercial products and can be purchased in the market.

[0022] Combination Figure 1 , a method for preparing a high-performance polyarylether battery separator, comprising the following steps: (1) Synthesizing a polyarylether polymer with a low benzonitrile group content; specifically, dissolving dihydric phenol, 2,6-dichlorobenzonitrile or 2,6-difluorobenzonitrile and 4,4-dichlorodiphenyl sulfone or 4,4-dichlorobenzophenone in an organic solvent NMP and toluene in a certain molar ratio, heating and stirring at 150°C for 2 h with potassium carbonate as a catalyst; then gradually raising the temperature of the reaction system to 175°C for 4 h; evaporating the toluene after the viscosity no longer increases, pouring the product into deionized water, and purifying to obtain the polyarylether copolymer with a low benzonitrile group content. The benzonitrile content in the polyarylether copolymer with a low benzonitrile group content is less than or equal to 35%, preferably 5%-25%. More specifically, the molar ratio of the 2,6-dichlorobenzonitrile or 2,6-difluorobenzonitrile (amount n), the dihydric phenol (amount n+m) and the 4,4-dichlorodiphenyl sulfone or 4,4-dichlorobenzophenone (amount m) is n:(n+m):m, wherein 0 <n / (n+m)≤35%。

[0023] (2) The polyarylether copolymer is dissolved in a high boiling point solvent and subjected to liquid phase heat treatment to obtain a cross-linked crude product. The cross-linked crude product is purified to obtain a polyarylether polymer containing a triazine ring structure, wherein a portion of the high boiling point solvent is retained as a solid pore-forming agent during the purification process; specifically, the high boiling point solvent is one or more of diphenyl sulfone, cyclopentane sulfone, and propylene glycol. More specifically, the temperature of the liquid phase heat treatment cross-linking is 290°C to 340°C, and the cross-linking time is 1 h to 4 h. The purification is as follows: the cross-linked crude product is crushed and washed with an organic solvent; the organic solvent is one or more of ethanol, acetone, and butanone; the purification process retains 0 to 20% of the high boiling point solvent in the product, and the organic solvent can dissolve and remove it in the later film formation process, thereby improving the uniformity of the pores in the diaphragm.

[0024] (3) The polyarylether copolymer containing a triazine ring structure is treated by electrospinning and solution phase transfer to form a porous membrane, and the porous membrane is dried to obtain a high-performance polyarylether battery separator.

[0025] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0026] Example 1 Synthesis of poly(arylether nitrile sulfone) with low benzonitrile group content: NMP (75 mL), toluene (25 mL), 2,6-dichlorobenzonitrile (0.054 mol), 4,4-dichlorodiphenyl sulfone (0.108 mol), K2CO3 (0.162×1.3 mol) and biphenyl (0.162×1.02 mol) were added to a 250 mL three-necked flask, slowly stirred and heated to 150°C for dehydration reaction, and then the temperature of the reaction system was gradually raised to 175°C for 4 h. After the viscosity no longer changed, the product was poured into 750 mL of deionized water for precipitation, and then washed and broken with deionized water after soaking for 2 h. The crude product was dried in an oven at 110°C for 3 h. Subsequently, the crude product was soaked in a hydrochloric acid solution with a mass fraction of 15% for 12 h, heated and boiled for 30 min, washed with deionized water, and dried by suction for 3 h to obtain poly(arylether nitrile sulfone) (PENS) with low benzonitrile group content.

[0027] Preparation of diaphragm: The polyarylether nitrile sulfone with low benzonitrile group content obtained above was dissolved in cyclopentane sulfone in a magnetic stirrer at a temperature of 60°C to obtain a casting solution with a PENS polymer mass fraction of 12%, and a film was cast on a clean and dry glass substrate with a casting knife. The glass substrate was then placed in deionized water to form a porous membrane. After the porous membrane was completely separated from the glass substrate, it was taken out and immersed in deionized water for 24 hours, and finally dried in an oven at 80°C for 24 hours to obtain a polyarylether nitrile sulfone battery diaphragm.

[0028] Example 2 Synthesis of poly(arylether nitrile sulfone) with low benzonitrile group content: NMP (75 mL), toluene (25 mL), 2,6-dichlorobenzonitrile (0.054 mol), 4,4-dichlorodiphenyl sulfone (0.108 mol), K2CO3 (0.162×1.3 mol) and biphenyl (0.162×1.02 mol) were added to a 250 mL three-necked flask, slowly stirred and heated to 150°C for dehydration reaction, and then the temperature of the reaction system was gradually raised to 175°C for 4 h. After the viscosity no longer changed, the product was poured into 750 mL of deionized water for precipitation, and then washed and broken with deionized water after soaking for 2 h. The obtained crude product was dried in an oven at 110°C for 3 h. Subsequently, the crude product was soaked in a hydrochloric acid solution with a mass fraction of 15% for 12 h, heated and boiled for 30 min, washed with deionized water, and dried by suction for 3 h to obtain poly(arylether nitrile sulfone) (PENS) with low benzonitrile group content.

[0029] Cross-linking of polyarylether nitrile sulfone: The polyarylether nitrile sulfone with low benzonitrile group content obtained above was dissolved in a high boiling point solvent diphenyl sulfone (mass ratio of 1:4), and heated and stirred at 320°C for 1 h. The system was then poured into deionized water to precipitate and broken up, and washed with deionized water 2-3 times. After filtration, it was dried in an oven at 110°C for 3 h. The product was then poured into anhydrous ethanol and stirred in a magnetic stirrer at 60°C for 1 h. After part of the diphenyl sulfone was precipitated, the product was dried in an oven at 110°C for 3 h to obtain a polyarylether nitrile sulfone copolymer containing a triazine ring structure. According to the mass calculation, 7.5 wt% of diphenyl sulfone was retained in the purified product after being dissolved in hot ethanol for 1 h.

[0030] Preparation of diaphragm: The polyarylether nitrile sulfone with low benzonitrile group content obtained above was dissolved in cyclopentane sulfone in a magnetic stirrer at a temperature of 60°C to obtain a casting solution with a PENS polymer mass fraction of 12%, and a film was cast on a clean and dry glass substrate with a casting knife. The glass substrate was then placed in deionized water to form a porous membrane. After the porous membrane was completely separated from the glass substrate, it was taken out and immersed in deionized water for 24 hours, and finally dried in an oven at 80°C for 24 hours to obtain a polyarylether nitrile sulfone battery diaphragm containing a triazine ring structure.

[0031] Example 3 Synthesis of poly(arylether nitrile sulfone) with low benzonitrile group content: NMP (75 mL), toluene (25 mL), 2,6-dichlorobenzonitrile (0.054 mol), 4,4-dichlorodiphenyl sulfone (0.108 mol), K2CO3 (0.162×1.3 mol) and biphenyl (0.162×1.02 mol) were added to a 250 mL three-necked flask, slowly stirred and heated to 150°C for dehydration reaction, and then the temperature of the reaction system was gradually raised to 175°C for 4 h. After the viscosity no longer changed, the product was poured into 750 mL of deionized water for precipitation, and then washed and broken with deionized water after soaking for 2 h. The crude product was dried in an oven at 110°C for 3 h. Subsequently, the crude product was soaked in a hydrochloric acid solution with a mass fraction of 15% for 12 h, heated and boiled for 30 min, washed with deionized water, and dried by suction for 3 h to obtain poly(arylether nitrile sulfone) (PENS) with low benzonitrile group content.

[0032] Cross-linking of polyarylether nitrile sulfone: The polyarylether nitrile sulfone with low benzonitrile group content obtained above was dissolved in a high boiling point solvent diphenyl sulfone (mass ratio of 1:4), and heated and stirred at 320°C for 2 h. The system was then poured into deionized water to precipitate and broken up, and washed with deionized water 2-3 times. After filtration, it was dried in an oven at 110°C for 3 h. The product was then poured into anhydrous ethanol and stirred in a magnetic stirrer at 60°C for 1 h. After part of the diphenyl sulfone was precipitated, the product was dried in an oven at 110°C for 3 h to obtain a polyarylether nitrile sulfone copolymer containing a triazine ring structure. According to the mass calculation, 7.6 wt% of diphenyl sulfone was still retained in the purified product after being dissolved in hot ethanol for 1 h.

[0033] Preparation of diaphragm: The polyarylether nitrile sulfone with low benzonitrile group content obtained above was dissolved in cyclopentane sulfone in a magnetic stirrer at a temperature of 60°C to obtain a casting solution with a PENS polymer mass fraction of 12%, and a film was cast on a clean and dry glass substrate with a casting knife. The glass substrate was then placed in deionized water to form a porous membrane. After the porous membrane was completely separated from the glass substrate, it was taken out and immersed in deionized water for 24 hours, and finally dried in an oven at 80°C for 24 hours to obtain a polyarylether nitrile sulfone battery diaphragm containing a triazine ring structure.

[0034] Example 4 NMP (75 mL), toluene (25 mL), 2,6-dichlorobenzonitrile (0.054 mol), 4,4-dichlorodiphenyl sulfone (0.108 mol), K2CO3 (0.162×1.3 mol) and biphenyl (0.162×1.02 mol) were added to a 250 mL three-necked flask, slowly stirred and heated to 150°C for dehydration reaction, and then the temperature of the reaction system was gradually raised to 175°C for 4 h. After the viscosity no longer changed, the product was poured into 750 mL of deionized water for precipitation, and then washed and broken with deionized water after soaking for 2 h. The crude product was dried in an oven at 110°C for 3 h. Subsequently, the crude product was soaked in a 15% hydrochloric acid solution for 12 h, heated and boiled for 30 min, washed with deionized water, and dried for 3 h to obtain poly (arylether nitrile sulfone) (PENS) with low benzonitrile group content.

[0035] Cross-linking of polyarylether nitrile sulfone: The polyarylether nitrile sulfone with low benzonitrile group content obtained above was dissolved in a high boiling point solvent diphenyl sulfone (mass ratio of 1:4), and heated and stirred at 320°C for 3 h. The system was then poured into deionized water to precipitate and broken up, and washed with deionized water 2-3 times. After filtration, it was dried in an oven at 110°C for 3 h. The product was then poured into anhydrous ethanol and stirred in a magnetic stirrer at 60°C for 1 h. After part of the diphenyl sulfone was precipitated, the product was dried in an oven at 110°C for 3 h to obtain a polyarylether nitrile sulfone copolymer containing a triazine ring structure. According to the mass calculation, 7.8 wt% of diphenyl sulfone was retained in the purified product after being dissolved in hot ethanol for 1 h.

[0036] Preparation of diaphragm: The polyarylether nitrile sulfone with low benzonitrile group content obtained above was dissolved in cyclopentane sulfone in a magnetic stirrer at a temperature of 60°C to obtain a casting solution with a PENS polymer mass fraction of 12%, and a film was cast on a clean and dry glass substrate with a casting knife. The glass substrate was then placed in deionized water to form a porous membrane. After the porous membrane was completely separated from the glass substrate, it was taken out and immersed in deionized water for 24 hours, and finally dried in an oven at 80°C for 24 hours to obtain a polyarylether nitrile sulfone battery diaphragm containing a triazine ring structure.

[0037] Example 5 Synthesis of poly(arylether nitrile sulfone) with low benzonitrile group content: NMP (75 mL), toluene (25 mL), 2,6-dichlorobenzonitrile (0.054 mol), 4,4-dichlorodiphenyl sulfone (0.108 mol), K2CO3 (0.162×1.3 mol) and biphenyl (0.162×1.02 mol) were added to a 250 mL three-necked flask, slowly stirred and heated to 150°C for dehydration reaction, and then the temperature of the reaction system was gradually raised to 175°C for 4 h. After the viscosity no longer changed, the product was poured into 750 mL of deionized water for precipitation, and then washed and broken with deionized water after soaking for 2 h. The crude product was dried in an oven at 110°C for 3 h. Subsequently, the crude product was soaked in a hydrochloric acid solution with a mass fraction of 15% for 12 h, heated and boiled for 30 min, washed with deionized water, and dried by suction for 3 h to obtain poly(arylether nitrile sulfone) (PENS) with low benzonitrile group content.

[0038] Cross-linking of polyarylether nitrile sulfone: The polyarylether nitrile sulfone with low benzonitrile group content obtained above was dissolved in a high boiling point solvent diphenyl sulfone (mass ratio of 1:4), and heated and stirred continuously at 320°C for 2 h. The system was then poured into deionized water to precipitate and then broken up, and washed repeatedly with deionized water 2-3 times. After filtration, it was dried in an oven at 110°C for 3 h, and then the product was poured into anhydrous ethanol and stirred continuously in a magnetic stirrer at a temperature of 60°C for 1 h. After filtering and drying, the product was dissolved in NMP for secondary purification: the solid-liquid mass ratio was 1:5, and the solvent was poured into deionized water to precipitate and then broken up, and then stirred in hot ethanol at a temperature of 60°C for 2 h to dissolve all the diphenyl sulfone and then filtered. The obtained powder was then dried in an oven at 110°C for 3 h to obtain a polyarylether nitrile sulfone copolymer containing a triazine ring structure.

[0039] Preparation of diaphragm: The polyarylether nitrile sulfone with low benzonitrile group content obtained above was dissolved in cyclopentane sulfone in a magnetic stirrer at a temperature of 60°C to obtain a casting solution with a PENS polymer mass fraction of 12%, and a film was cast on a clean and dry glass substrate with a casting knife. The glass substrate was then placed in deionized water to form a porous membrane. After the porous membrane was completely separated from the glass substrate, it was taken out and immersed in deionized water for 24 hours, and finally dried in an oven at 80°C for 24 hours to obtain a polyarylether nitrile sulfone battery diaphragm containing a triazine ring structure.

[0040] Example 6 Synthesis of poly(arylether nitrile sulfone) with low benzonitrile group content: NMP (75 mL), toluene (25 mL), 2,6-dichlorobenzonitrile (0.054 mol), 4,4-dichlorodiphenyl sulfone (0.108 mol), K2CO3 (0.162×1.3 mol) and biphenyl (0.162×1.02 mol) were added to a 250 mL three-necked flask, slowly stirred and heated to 150°C for dehydration reaction, and then the temperature of the reaction system was gradually raised to 175°C for 4 h. After the viscosity no longer changed, the product was poured into 750 mL of deionized water for precipitation, and then washed and broken with deionized water after soaking for 2 h. The crude product was dried in an oven at 110°C for 3 h. Subsequently, the crude product was soaked in a hydrochloric acid solution with a mass fraction of 15% for 12 h, heated and boiled for 30 min, washed with deionized water, and dried by suction for 3 h to obtain poly(arylether nitrile sulfone) (PENS) with low benzonitrile group content.

[0041] Cross-linking of polyarylether nitrile sulfone: The polyarylether nitrile sulfone with low benzonitrile group content obtained above was dissolved in a high boiling point solvent diphenyl sulfone (mass ratio of 1:4), and heated and stirred continuously at 320°C for 3 h. The system was then poured into deionized water to precipitate and then broken up, and washed repeatedly with deionized water 2-3 times. After filtration, it was dried in an oven at 110°C for 3 h, and then the product was poured into anhydrous ethanol and stirred continuously in a magnetic stirrer at a temperature of 60°C for 1 h. After filtering and drying, the product was dissolved in NMP for secondary purification: the solid-liquid mass ratio was 1:5, and the solvent was poured into deionized water to precipitate and then broken up, and then stirred in hot ethanol at a temperature of 60°C for 2 h to dissolve all the diphenyl sulfone and then filtered. The obtained solid was dried in an oven at 110°C for 3 h to obtain a polyarylether nitrile sulfone copolymer containing a triazine ring structure.

[0042] Preparation of diaphragm: The polyarylether nitrile sulfone with low benzonitrile group content obtained above was dissolved in cyclopentane sulfone in a magnetic stirrer at a temperature of 60°C to obtain a casting solution with a PENS polymer mass fraction of 12%, and a film was cast on a clean and dry glass substrate with a casting knife. The glass substrate was then placed in deionized water to form a porous membrane. After the porous membrane was completely separated from the glass substrate, it was taken out and immersed in deionized water for 24 hours, and finally dried in an oven at 80°C for 24 hours to obtain a polyarylether nitrile sulfone battery diaphragm containing a triazine ring structure.

[0043] Test example 1. The polyarylethernitrilesulfone battery separators obtained in Examples 1 to 6 were named PENS-C0, PENS-C1, PENS-C2, PENS-C3, PENS-C4, and PENS-C5, respectively, and infrared radiation thermal imaging tests were performed with commercial Celgard2500 separators. The test results are shown in FIG. Figure 2As shown in the figure. The figure shows the thermal distribution of various membranes at different temperatures for 20 minutes. Compared with the PENS membrane, the Celgard2500 membrane has undergone obvious deformation at 120°C, while the PENS-C0 membrane has not undergone obvious deformation at 150°C. The PENS-C1, PENS-C2, PENS-C3, PENS-C4, and PENS-C5 membranes have not undergone obvious deformation at 220°C, which shows the excellent high temperature resistance of the PENS membrane. However, the dimensional stability of the membrane prepared by PENS with some diphenyl sulfone solvent at high temperature is better than that of the PENS membrane with all diphenyl sulfone removed, indicating that the pores of the membrane prepared by the phase transfer method of PENS containing diphenyl sulfone are more uniform and more stable.

[0044] 2. The polyarylether nitrile sulfone battery separators obtained in Examples 1 to 6 were tested for performance with the commercial Celgard 2500 separator. A universal mechanical testing machine was used to test the stress-strain of various separators, and the tensile strength and elongation at break of the separators were obtained; at room temperature, the wettability of the prepared separators to the liquid electrolyte was studied, wherein the liquid electrolyte was 1.0 M LiPF6 in EC:DMC=1:1 Vol%; the ionic conductivity of the separator was calculated by electrochemical impedance spectroscopy (EIS), and the separator was placed between two stainless steel gaskets during the test.

[0045] The test data is shown in Table 1.

[0046] As shown in Table 1, the tensile strength and elongation at break of the PENS membrane prepared by the present invention are higher than those of the Celgard2500 membrane, indicating that the PENS membrane has excellent mechanical properties. As the crosslinking time increases, the tensile strength of the PENS membrane also gradually increases, while the elongation at break gradually decreases, mainly because the triazine ring with stable structure is generated by the crosslinking reaction, so that the sample presents a network structure, resulting in an increase in its mechanical properties. The mechanical strength and ionic conductivity of the membrane prepared by the PENS with some diphenyl sulfone solvent retained are higher than those of the PENS membrane with all diphenyl sulfone removed, which also shows that retaining some diphenyl sulfone in the PENS can effectively improve the mechanical strength and ionic conductivity of the porous membrane prepared subsequently, and also simplifies the purification step of the crosslinked product. Moreover, the electrolyte contact angle of the PENS membrane prepared by the present invention is smaller than that of the Celgard2500 membrane, and the ionic conductivity is higher than that of the Celgard2500 membrane, indicating that the PENS membrane has good electrolyte wettability, which is more conducive to the migration of lithium ions.

[0047] Table 1 Diaphragm performance Celgard2500 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Tensile strength / Mpa 10.37 12.73 12.85 13.11 14.83 12.79 12.83 Elongation at break / % 17 23.8 23.3 20.6 18.6 22.5 19.8 Electrolyte contact angle / ° 66.09 34.01 22.5 23.2 21.3 22.6 22.9 <![CDATA[Ionic conductivity / 10 -3 S / cm]]> 0.53 0.86 0.98 1.23 1.16 0.95 1.17 The polyarylether nitrile sulfone diaphragms obtained in Examples 1 to 6 and the commercial Celgard2500 diaphragm were assembled in CR2032 button cells, wherein the positive electrode material was a LiFePO4 electrode, the negative electrode was a lithium sheet, the liquid electrolyte was 1.0 M LiPF6in EC:DMC=1:1 Vol%, and all the batteries were assembled in a vacuum glove box. Room temperature and high temperature long cycle charge and discharge performance tests were performed on the battery test system, wherein the high temperature test was to place the button cell and the fixture in an oven at 80°C, and the test voltage range was 2.2-4.2V.

[0048] Figure 3 (a) shows the discharge specific capacity and coulombic efficiency of lithium-ion batteries based on various types of separators at room temperature at a current density of 0.5C. The figure shows that the lithium-ion battery based on the PENS-C2 separator has a higher initial capacity and can still maintain 153.6 mAh g after 100 charge and discharge cycles. -1 The high discharge capacity and capacity retention rate are 98.08%. Figure 3 (b) shows the discharge capacity of lithium-ion batteries based on various types of diaphragms at a current density of 0.5C at 80°C. It can be seen that the discharge capacity of the battery with Celgard2500 diaphragm completely dropped to 0 after 20 charge and discharge cycles, and the battery could not operate normally. This may be due to the shrinkage of the diaphragm caused by high temperature, and a short circuit occurred inside the battery. The lithium-ion battery with PENS diaphragm still showed a high discharge capacity and coulomb efficiency. It can also be seen that the initial capacity of the diaphragm prepared by PENS with some diphenyl sulfone solvent retained is higher than that of the diaphragm with all diphenyl sulfone removed, indicating that the pores of the PENS diaphragm with some diphenyl sulfone retained are more uniform, and the prepared battery performance is better.

[0049] In summary, according to the embodiments of the present invention, a polyarylether (polyarylether nitrile sulfone and polyarylether nitrile ketone, etc.) with a benzonitrile structure terminated with a chain end phenolic hydroxyl group is used as a matrix resin, and a triazine ring structure is generated by cross-linking through solution heat treatment in a high-boiling point solvent; the cross-linking degree of the polyarylether is regulated by controlling the liquid phase cross-linking reaction, and finally a battery separator is prepared; the high-boiling point solvent that has not been washed clean can also be used as a pore-forming placeholder for the final formation of a porous membrane, further improving the uniformity of the pores. The overall simple and controllable preparation method can be used to prepare a polyarylether battery separator containing a triazine ring structure with high flame retardancy, high strength, high temperature resistance and impact resistance, and can be used in lithium-ion, sodium-ion and other batteries, thereby improving the performance of the battery.

[0050] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily referring to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.

[0051] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a high-performance polyarylether battery separator, characterized in that: The following steps are involved: (1) Synthesis of polyarylene ether copolymers with low benzonitrile group content; (2) dissolving the polyarylether copolymer in a high boiling point solvent, heating under the action of the high boiling point solvent to carry out liquid phase crosslinking to obtain a crosslinked crude product, and purifying the crosslinked crude product to obtain a polyarylether copolymer containing a triazine ring structure, wherein a portion of the high boiling point solvent is retained during the purification process as a solid pore-forming agent; (3) The polyarylether copolymer containing a triazine ring structure is treated by electrospinning and solution phase transfer to form a porous membrane, and a high-performance polyarylether battery separator is obtained after drying.

2. The preparation method according to claim 1, characterized in that The content of benzonitrile in the polyarylene ether copolymer with low benzonitrile group content is less than or equal to 35%.

3. The preparation method according to claim 2, characterized in that: The polyarylether copolymer is polyarylether nitrile sulfone or polyarylether nitrile ketone, wherein the proportion of the aromatic sulfone or aromatic ketone structure is greater than or equal to 65% and less than 100%.

4. The preparation method according to claim 1, characterized in that: Step (1) includes: Dihydric phenol, 2,6-dichlorobenzonitrile or 2,6-difluorobenzonitrile and 4,4-dichlorodiphenyl sulfone or 4,4-dichlorobenzophenone are dissolved in an organic solvent N-methylpyrrolidone (or N,N-dimethylformamide or N,N-dimethylacetamide or cyclopentane sulfone) and toluene, and a nucleophilic substitution condensation polymerization reaction is carried out with potassium carbonate as a catalyst; after the viscosity no longer increases, toluene is evaporated, and the product is poured into deionized water, and purified to obtain the polyarylene ether copolymer with a low benzonitrile group content.

5. The preparation method according to claim 4, characterized in that: The molar ratio of the 2,6-dichlorobenzonitrile or 2,6-difluorobenzonitrile, the dihydric phenol and the 4,4-dichlorodiphenyl sulfone or 4,4-dichlorobenzophenone is n:(n+m):m, wherein 0 <n / (n+m)≤35%。 6. The preparation method according to claim 1, characterized in that: The high boiling point solvent in the liquid phase crosslinking is one or more of diphenyl sulfone, cyclopentane, and glycerol.

7. The preparation method according to claim 1, characterized in that: In step (2), the temperature of liquid phase crosslinking is 290°C to 340°C, the crosslinking time is 1 h to 4 h, and the crosslinking degree of the crosslinked product can be controlled by the solution viscosity.

8. The preparation method according to claim 1, characterized in that: In step (2), purification is as follows: the cross-linked crude product is crushed and washed with an organic solvent, and during the purification process, 0-20% of the high boiling point solvent is retained in the product.

9. The preparation method according to claim 8, characterized in that: The organic solvent is one or more of ethanol, acetone and butanone.

10. Use of the high-performance polyarylether battery separator prepared by the preparation method according to any one of claims 1 to 9 in lithium-ion batteries or sodium-ion batteries.

Citation Information

Patent Citations

  • High-temperature resistant polyarylene ether nitrile lithium-ion battery separator materials, their preparation methods and applications

    CN112898560B

  • Polyaryl ether nitrile and producing process thereof

    CN1124745A

  • High-temperature-resistant polyarylene ether nitrile lithium ion battery diaphragm material as well as preparation method and application thereof

    CN112898560A

  • Ultra-low dielectric constant cross-linked polyarylene ether nitrile film and preparation method thereof

    CN114015039A

  • Polyaryletherketone diaphragm as well as preparation method and application thereof

    CN115295958A

Cited By

  • Modified diaphragm for improving deposition behavior of lithium metal as well as preparation method and application of modified diaphragm

    CN121216050A